PERANCANGAN APLIKASI KLINIK UNIRA BERBASIS WEB UNTUK OPTIMALISASI PELAYANAN - Syahroni, Abd. Wahab; Rofiq Hafsi, Ainur; Ramadhani, Nilam; Said, Badar (Antivirus : Jurnal Ilmiah Teknik Informatika, 2022)
UNIRA Clinic still uses manual books in collecting data on its service activities. The services provided by the UNIRA Clinic include blood checks, blood pressure checks, and drug administration based on the patient's diagnosis. This study aims to design and build an application for the UNIRA Clinic that can assist in recording patient check up history and facilitate it in recapitulation so that it can be an answer to the shortcomings of recording patient check up manually using books. The application was built using the prototype method, database design using CDM and PDM, database implementation on MySQL, implementation of programming languages ​​with Javascript and PHP. Measurement of application use satisfaction using a Likert scale. Of the 10 respondents who have answered the questionnaire, it can be concluded that the respondents strongly agree that this application has been built in accordance with the existing system flow at the UNIRA Clinic with a Likert scale result of 98%.